DEVELOPING FLASHCARD AS A MEDIA TO TEACH SPEAKING FOR SEVENTH GRADE STUDENTS AT MTS AL-WASHLIYAH KOLAM - Dinda Ervina Putri Sipayung; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
The study aimed to develop learning media in Speaking Descriptive Text forGrade VII of Junior High School Students. This study used Research andDevelopment (R&D) design through six stages; gathering information and data,analyzing data, designing materials, validating by experts, revising, and finalproduct. The subject of the study was Grade VII of MTs Al-Washliyah Kolam.The instruments of data collection were gathered by administring interview anddistributing questionnaire. The study was conducted by interviewing the Englishteacher and distributing questionnaire to 30 respondents to get the students’ needs.The interview and questionnaire results proved that the students need Englishlearning media which can motivate the students to understand about speakingdescriptive text. The product had been validated by the experts namely Englishlecturer and English teacher. The product result was Flashcard which ismodifying to playing game based on the rules game. The result of experts’validation showed that the media was an appropriate media to be used onspeaking descriptive text by getting the average percentage 95% categorizedexcellent.